2004
DOI: 10.1111/j.1365-2966.2004.07378.x
|View full text |Cite
|
Sign up to set email alerts
|

Protostellar collapse induced by compression - II. Rotation and fragmentation

Abstract: We investigate numerically and semi-analytically the collapse of low-mass, rotating prestellar cores. Initially, the cores are in approximate equilibrium with low rotation (the initial ratio of thermal to gravitational energy is α 0 0.5, and the initial ratio of rotational to gravitational energy is β 0 = 0.02-0.05). They are then subjected to a steady increase in external pressure. Fragmentation is promoted -in the sense that more protostars are formed -both by more rapid compression, and by higher rotation (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 70 publications
(118 reference statements)
5
68
0
1
Order By: Relevance
“…They found that fragmentation is promoted when both the rotation of the cloud and the compression rate are faster. In this sense, our models with the more massive envelopes and smaller initial rotation velocities would be similar to those of Hennebelle et al (2004) with a low compression rate.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 85%
See 1 more Smart Citation
“…They found that fragmentation is promoted when both the rotation of the cloud and the compression rate are faster. In this sense, our models with the more massive envelopes and smaller initial rotation velocities would be similar to those of Hennebelle et al (2004) with a low compression rate.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 85%
“…But as we observed in models A3 and B3, there is not enough rotation inertia for the spiral arms to grow up, and most of the particles go directly to the central clump. Hennebelle et al (2004) have considered the collapse of a low-mass, rotating prestellar core which is subject to a steady increase of external pressure. They found that fragmentation is promoted when both the rotation of the cloud and the compression rate are faster.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Apart for δ, which is a coefficient on the order of a few, the first term simply correponds to the singular isothermal sphere (Shu 1977) while the second one is a correction that must be included when rotation is significant, particularly in the inner part of the envelope close to the disc edge, as discussed in Hennebelle et al (2004) (see their appendix and Fig. 2).…”
Section: Timescales and Equilibriamentioning
confidence: 99%
“…In the highly dynamic scenario the collapse of a prestellar core is far more likely to lead to fragmentation and the formation of multiple systems (e.g., Whitworth et al 1995;Turner et al 1995;Whitworth et al 1996;Klein et al 2001Klein et al , 2003Bate et al 2002aBate et al ,b, 2003Bonnell et al 2003;Delgado-Donate 2003, 2004Goodwin et al 2004a,b;Hennebelle et al 2003Hennebelle et al , 2004. This is because in the highly dynamic scenario prestellar cores are formed non-quasistatically and therefore (a) they are launched directly into the non-linear regime of gravitational collapse, and (b) they are likely to have retained some internal turbulence.…”
Section: Introductionmentioning
confidence: 99%